BASLAWÍSH KLASSLARDA MUZÍKA PÁNIN OQÍTÍWDA OYÍN TEXNOLOGIYaLARÍNAN PAYDALANÍW - Axetova, G.J. (SCIENCE and SOCIETY, 2022)
This article talks about the use of gaming technology in music lessons. The concepts of notes, the stave, the location of notes in the stave are considered. The rules of the game are marked.
Keywords: game methods; music; musical dominoes; notes; stave; octave